ANALISIS PERUBAHAN PENGGUNAAN LAHAN UNTUK PERMUKIMAN DI KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - Ratna Apriani Apriani; triyatno triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to determine: (1) the area and changes in land use for settlements from 2010 to 2020, and (2) the impact of changes in land use for settlements on agricultural productivity in Ampek Angkek District. This research is quantitative descriptive. The data analysis technique used is image interpretation for land use and overlapping techniques for land use changes as well as primary data collection with interviews for agricultural productivity. The results showed that (1) the area and land use changes for settlements in Ampek Angkek District from 2010 - 2020 amounted to 158.66 Ha, where in 2010 it was 210.68 Ha and in 2020 it was 369.34 Ha. (2) Changes in land use for settlements have an impact on agricultural productivity, especially on the area of ​​land used as a factor of agricultural productivity, and is evidenced by a decrease in lowland rice productivity of 2.35 tons/ha from 2010 and 2020.